"My Body Spoke to Me": "Marginal" Organs, Metonymic Somatization, and the Pain of Social Selection. (5th October 2018) - Amir, Dana; Shoshana, Avihu
Abstract: Through in‐depth interviews, this article examines the accounts of subjects who, due to their selfhood and bodies being marked as "ethnic, " do not pass the selection process to enter night clubs in Tel Aviv. Their experiences of pain are expressed via a connection between the social, the physical and the mental, and indicates a unique somatic awakening. This awakening is expressed through an experience of body parts being perceived as "transparent" or "marginal" and not receiving phenomenological and somatic attention in everyday life. Using psychoanalytical model related to the symbolization levels of the somatic awakening, we propose interpreting this awakening ‐ of the "marginal" ‐ as metonymic somatic evidence. This awakening and the interpretation of it create continuity between the experience of "marginal" organs and the experience of marginality in the nighttime arena of ethnic selection. The discussion suggests that the sources of this mental‐somatic awakening are related to the transformation of the private subject into a symbolic type ("the guy that doesn't pass selection"), which in turn expresses the collapse of the inimitable.